ANALISIS LOCATIONAL QUOTIENT DAN SHIFT SHRE TERHADAP PEREKONOMIAN WILAYAH KABUPATEN KLATEN TAHUN 20015 – 2019 - suparyanto, suparyanto suparyanto (Universitas Slamet Riyadi, 2020)
This study aims to analyze the economy of the Klaten Regency in Central Java Province during 2015 – 2019 using Locational Quatient (LQ) and Shift Share analysis. Through this research, the most competitive base and business fields are obtained. The research method used is a quantitative method. The data used is secondary, the constant price GRDP data of Klaten Regency and Central Java Province during 2015 – 20119. The analytical tool used in this study is the Locational Quatient (LQ) analysis and Shift Share analysis. The results of this study indicate: (1) From 17 business fields in Klaten Regency, in 2015 – 2019, 8 business fields were found including the basic sectors, namely: (1) Mining and Excavation, (2) Procurement of Electricity and Gas, (3) Wholesale and Retail Trade, Car and Motorcycle Repair, (4) Provision of Accommodation and Food and Beverage, (5) Financial Services and Insurance, (6) Educational Services, (7) Health and Social Assistance Services, and (8) Services the other. Specifically in 2019 there will be an increase in one base business field, namely the manufacturing industry field, so that in 2019 there will be 9 base business fields; (2) The business field that has the highest competitiveness or competitive advantage is the processing industry. Keywords: locational quatient, shift share, base business field, competitive advantage.